Il lessico miceneo riferito ai cereali - Vittiglio, Nicola Antonello (Strumenti per la didattica e la ricerca, 2017)
This book constitutes a study of the lexicon of cereals as witnessed by the Mycenaean inscriptions. The study focuses both on the nouns used to designate cereals, on their compounds and derivatives, and on the terms with which they relate (adjectives, theonyms, toponyms, etc.). The volume is divided into three chapters. The first chapter analyses the six Mycenaean terms together with their derivatives and compounds - phonetically transcribed - which designate cereals or include their names: wheat, barley, wheat flour, barley flour, bakers (= those who bake bread) together with others nouns belonging to the same semantic field, such as seed. The second chapter focuses on three Mycenaean logograms designating cereals: *120, *121 and *129, interpreted respectively as wheat, barley and flour. The third chapter describes the wide set of terms appearing contextually in the inscriptions in which cereals are attested, and groups them according to their meaning: human and divine recipients, toponyms, adjectives, other administrative terms, etc. Finally, the conclusions present an overall assessment of the data analysed in the previous chapters, that is an assessment affecting the economic, political, social and religious sphere of the Mycenaean civilisation.